Diagnosing, Managing and Understanding the Impact of Co-Occurring Conditions in Autism Spectrum Disorder on Quality of Life - Xavier, Milagrin; Ravi, Priyadharsini; Murthy, Preethi Bala Dhakshina; Singam, Ann Jency Arul Durai; Mohandass, Subhalakshmi (Indian Journal of Pharmacy Practice)
Autism Spectrum Disorder (ASD) is a multifaceted neurodevelopmental disorder characterized by difficulties in social interaction, restricted interests and repetitive behaviors. It frequently coexists with a variety of other medical, psychiatric and developmental conditions, such as anxiety, ADHD, epilepsy, gastrointestinal problems and sleep disturbances. These co-occurring conditions can greatly affect the quality of life for individuals with ASD, adding complexity to diagnosis and treatment. Successfully managing ASD and its associated conditions requires a comprehensive, multidisciplinary approach, incorporating behavioral therapies, pharmacological treatments and personalized support systems. A deep understanding of how these conditions interact and influence overall functioning in individuals with ASD is essential for improving outcomes. This paper investigates the relationship between ASD and its commonly co-occurring conditions, their effect on quality of life and the importance of timely and holistic management. It also explores the role of family and community support, as well as future research directions aimed at developing more effective treatments and interventions.
Keywords: Autism Spectrum Disorder (ASD); Co-occurring conditions; Neurodevelopmental disorders; Pharmacological treatment and Future research in ASD treatment